High school students' mathematical modeling skills in problem-based learning (PBL). (March 2020) - Sakinah, A R; Hiltrimartin, C; Hartono, Y; Indaryanti
Abstract: This study aims to know the mathematics modeling skill in Problem-based learning (PBL) in high school. Data were collected by test method in Students grade 10 SMA Negeri 2 in system of linear equation in three variable material. Based on the results of the research analysis, 64.7% of categorized learners have excellent modeling skills, 32.5% of the categories are good and 2% are poor. That is because students do not understand the problem, even though one of the goals of mathematics learning is students can solve mathematical problems which are covered by understanding problems and modeling problems into mathematical form. To realize these learning objectives the use of appropriate learning models is an important aspect. One learning model that can be used so that students have good modeling skill is Problem-based learning (PBL). PBL has a focus learning on contextual problems, so students can understand the problem and able to make mathematical models of the contextual problems presented.